Risk factors and clinical profile in patients of acute kidney injury - Kumar, Ajay; Kaur, Rupinderjeet; Bhatia, Lovleen; Singh, Ardaman; Bansal, Richa (International Journal of Research in Medical Sciences, 2023)
Background: Acute kidney injury (AKI) is an outcome of multiple etiologies and is mostly reversible. This hospital based cross-sectional observational study was aimed to study the risk factors and clinical profile in patients of AKI. Methods: Sixty AKI patients diagnosed by acute kidney injury network criteria as suggested by kidney disease improving global outcomes clinical practice guidelines were enrolled. Patients with preexisting chronic kidney disease were excluded. Relevant data was recorded and analyzed statistically. Data were compiled using the Statistical Package for the Social Sciences version 17. Regression analysis was done for determining the association of various variables for mortality. P<0.05 was considered statistically significant. Results: The mean age of patients was 52.63±15.58 years with male:female ratio of 2:1. 20% of cases had co-morbidities, the most common co-morbidity being diabetes mellitus with hypertension in 15% of cases. The most common presenting symptom was vomiting (63.3% of patients); sign was hypotension and tachycardia (46.7% each). sepsis was the most common cause of AKI affecting 38 (63.33%) cases. Majority of the cases were non oliguric 81.7%. Pre-renal variety was found in 41.7% patients in this area. Hence, this study suggested a scope for reducing morbidity and mortality associated with AKI if these preventable factors leading to Pre-Renal AKI and sepsis, being an important risk factor for AKI are controlled and prevented as far as possible. Conclusions: The study concluded that sepsis was the most common cause of AKI.